National Evaluation of the Fighting Back Program: General Population Surveys, 1995-1999 - Saxe, Leonard ([Verlag nicht ermittelbar], 2003)
This study was designed as part of a multi-method assessment of Fighting Back, a community-based drug abuse prevention program funded by the Robert Wood Johnson Foundation. Fighting Back was implemented in 14 medium-sized, primarily urban communities in 12 states. To assess whether the Fighting Back program led to changes in alcohol and other drug (AOD) patterns and attitudes, the evaluation conducted general population surveys of residents aged 16-44 in 12 Fighting Back program communities and 29 comparison communities. Conducted in three waves -- 1995, 1997, and 1999 -- these surveys constitute the Community Survey (Part 1). To provide comparative national trend data, the National Survey (Part 2) was administered, concurrently with the second and third waves, to a national sample of the non-rural general population aged 16-44 using the same survey instrument as the Community Survey. The strategy for question design was to replicate previously validated questions from national surveys of substance use and dependency, including the National Household Survey of Drug Abuse, the National Comorbidity Study, and the Monitoring the Future study of American youth. Respondents reported their AOD use, their friends' AOD use, their attitudes about AOD use, how their friends felt about AOD use, and their perceptions of drug sales, crime, and other aspects of their neighborhood. In addition, the surveys collected information on volunteerism, crime victimization, health and mental health, knowledge and utilization of AOD treatment services, attendance in drug education courses or lectures in school, and opinions on marijuana legalization. Background variables include sex, race, Hispanic origin, household composition, marital/cohabitation status, education status and achievement, employment status, occupation, religious preference, religiosity, and income.